Eleven on top - Evanovich, Janet (New York : St. Martin's Press, 2005)
Hoping to discontinue her career as a bounty hunter for something safer, Stephanie Plum is inadvertently drawn into a case that is complicated by her tangled love life, her chaotic family, and her penchant for wrecking cars.
Keywords: Bounty hunters -- Fiction